Sinus opacification in the intensive care unit patient. (7th September 2016) - Huyett, Phillip; Lee, Stella; Ferguson, Berrylin J.; Wang, Eric W.
Abstract : Objectives/Hypothesis: The significance of sinus opacification in intensive care unit (ICU) patients remains uncertain. Our objectives were to determine the baseline incidence and risk factors associated with the development of radiographic sinus abnormalities in the ICU population. Methods: A retrospective study of head computed tomography scan or magnetic resonance imaging from April 2013 through April 2014 of 612 neurologic ICU patients at the University of Pittsburgh Medical Center Presbyterian Hospital, Pittsburgh, Pennsylvania, was performed. Images were scored by the Lund‐Mackay system (LMS). Exclusion criteria included prior sinus or skull base surgery, history of sinonasal malignancy, facial fractures, ICU admission less than 3 days, or inadequate imaging. Results: At the time of admission, 40.7% of patients had a LMS greater than zero (mean 2.2). Worsening sinus opacification occurred in 42.6% of patients (mean highest LMS 4.6) during ICU admission. There was a peak between days 8 and 10, during which 65% of scans exhibited worsening opacification compared to baseline. On multivariate analysis, risk factors associated with increased sinus opacification (higher LMS) included the presence of an endotracheal tube (odds ration [OR] 3.28, P < .001) or nasogastric tube (OR 3.34, P < .001) and increased length of stay (OR 2.50, P < .001). Age greater than 60 was found to be protective for the development of worsening sinus opacification (OR 0.57, P = .007). Conclusion: Using serial imaging and comparison control groups, this study finds that there is a high baseline incidence of sinus opacification in the ICU population. Prolonged length of stay, younger age, and presence of nasogastric or endotracheal tubes all corresponded to worsening LMS. Level of Evidence: 4. Laryngoscope, 126:2433–2438, 2016